2015
DOI: 10.3171/2014.9.jns141550
|View full text |Cite
|
Sign up to set email alerts
|

Actual and projected incidence rates for chronic subdural hematomas in United States Veterans Administration and civilian populations

Abstract: The incidence of chronic SDH is rising; SDH is projected to become the most common cranial neurosurgical condition among adults by the year 2030.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
179
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(184 citation statements)
references
References 33 publications
3
179
0
2
Order By: Relevance
“…3 A study from the United States also showed an increase in the incidence rates of subacute or chronic subdural hematoma, and the researchers predicted that subacute or chronic subdural hematoma will become the most common cranial neurosurgical condition among adults in 2030. 2 Steep increases in incidence rates of subdural hematoma among older patients (aged 75-89 years) were found in the present study. Furthermore, the present results emphasize that the major shifts in patterns of antithrombotic drug treatment for older individuals, 28 and the increasing use of more aggressive antithrombotic regimens, have already had a major effect on subdural hematoma incidence.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…3 A study from the United States also showed an increase in the incidence rates of subacute or chronic subdural hematoma, and the researchers predicted that subacute or chronic subdural hematoma will become the most common cranial neurosurgical condition among adults in 2030. 2 Steep increases in incidence rates of subdural hematoma among older patients (aged 75-89 years) were found in the present study. Furthermore, the present results emphasize that the major shifts in patterns of antithrombotic drug treatment for older individuals, 28 and the increasing use of more aggressive antithrombotic regimens, have already had a major effect on subdural hematoma incidence.…”
Section: Discussionsupporting
confidence: 59%
“…2,3 Subacute or chronic subdural hematoma incidence is predicted to further increase due to the aging population. 2 Use of antithrombotic drugs has been associated with increased subacute or chronic subdural hematoma risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of CSDH is approximated between 8.2 to 14 persons per 100,000/year showing a trend towards an increase in the incidence of CSDH in the coming decades [1, 2]. CSDHs have several established predisposing risk factors such as advanced age, previous trauma to the head, anticoagulant and antiplatelet medication, and history of alcohol abuse contributing to global cerebral atrophy [1, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…Even though chronic SDH is one of the most common neurosurgical conditions, only a few studies have investigated its incidence in Caucasian populations in the era of modern brain imaging. The annual incidence has been found to be 8.2/100,000 in population over 65 years of age in North Wales [2] and estimated to be 16.8/100,000 among men 60-99 years of age in the United States [3]. We found that among patients with HD, the incidence rate was 68.3/100,000 person-years.…”
Section: Discussionmentioning
confidence: 87%